PREVENTION OF EARLY POSTOPERATIVE HEART FAILURE AFTER CORONARY ARTERY BYPASS GRAFTING (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background: Early postoperative heart failure (EPOHF) after coronary artery bypass grafting (CABG), often reported as low cardiac output syndrome (LCOS), is a frequent cause of prolonged intensive care and early complications. We evaluated a protocolized prophylaxis bundle aimed at preventing EPOHF in a single cardiac surgery center.
Keywords: Coronary artery bypass grafting; early postoperative heart failure; low cardiac output syndrome; goal-directed hemodynamic therapy; enhanced recovery; inotropes.